Risk Factors and Management of Dental Erosion and Traumatic Dental Injuries among School Children: https://doi.org/10.5281/zenodo.18103737 (Pakistan Journal of Medical & Cardiological Review, 2025)
BackgroundDental erosion and traumatic dental injuries (TDIs) are increasingly prevalent oral health problems among children, particularly in low- and middle-income countries where preventive dental services are limited. These conditions can adversely affect oral function, esthetics, and quality of life if not identified and managed early.ObjectivesTo determine the risk factors of dental erosion and traumatic dental injuries among school-going children.MethodsA cross-sectional analytical study was conducted among 360 children aged 6 to 12 years selected through multistage random sampling from public and private schools. Dental erosion and TDIs were assessed clinically using standardized criteria. Data on sociodemographic characteristics, dietary habits, oral hygiene practices, trauma history, and treatment-seeking behavior were collected using a structured questionnaire. Data was analyzed using descriptive statistics, chi-square tests, and multivariable logistic regression analysis.ResultsThe prevalence of dental erosion was 33.1%, while traumatic dental injuries were observed in 21.4% of children. Frequent consumption of carbonated drinks, brushing less than twice daily, and lower parental education were significant predictors of dental erosion (p < 0.05). Male gender, participation in outdoor sports, and increased overjet were significantly associated with TDIs (p < 0.05). Only 39.0% of children with TDIs received professional dental treatment.ConclusionsDental erosion and traumatic dental injuries are common among Pakistani children and are influenced by modifiable behavioral and environmental factors. School-based preventive programs and improved parental awareness are urgently needed.